INSPECTION INTERVAL DETERMINATION OF OFFSHORE STRUCTURE USING RISK RELIABILITY BASED UNDERWATER INSPECTION (RREBUI) - Falahi, Fajrin
Inspection of the structure of offshore platforms in Indonesia has been using the TBI (time based inspection) system. However, periodic inspection of offshore platforms based on time has a weakness because it does not differentiate between the time and scope of the inspection to be carried out on offshore platforms, be it old or new structures, which are adjusted to the characteristics of the offshore platforms and do not take into account randomness factors both from capacity or load. In this study, the method of risk reliability based underwater inspection (RReBUI) was carried out as an alternative method in determining the inspection of the fixed platform structure in the Natuna Sea where risk is defined as the multiplication of probability of failure (PoF) with the factor consequence of failure (CoF). The calculation of PoF is carried out in a quantitative way based on the collapse and fatigue structure failure mode with vraiables of wave height and wave period as random parameters using the First Order Reliability Moment II (FORM II) method reliability analysis. Meanwhile, CoF and inspection time will refer to the API RP- 2SIM standard. The results of a case study conducted on a fixed type offshore platform structure with a number of 8 legs in the Natuna Sea found that the global risk assessment based on the failure mode of collapse obtained a risk ranking value of 5, with a PoF value of 1 and CoF of 5 so that the survey inspection interval level I and II are 1 year and 4 years, respectively. Meanwhile, the local risk assessment based on the fatigue failure mode obtained a risk value of 15 for vertical bracing and 25 for the leg with inspection intervals at the joint with 6 years and 12 years interval respectively.